The Combination of Youtube and Wordwall In Arabic Language Learning: Perspectives of Teachers and Students of MAN 2 Yogyakarta - Rasyidah, Nafiatur; Al Anshory, Abdul Muntaqim; Hasaniyah, Nur; Uqba, M Sholih Salimul (IAIN Bone, 2025)
Among the technology products that are widely used in education, especially Arabic language learning, are YouTube and Wordwall. This is what is applied in Arabic language learning at MAN 2 Yogyakarta. This paper aims to reveal how the combination of YouTube and Wordwall in Arabic language learning that is seen from the perspective of teachers and students. This research is a descriptive research with qualitative approach and case study type. This research was conducted at MAN 2 Yogyakarta with the research subjects were Arabic language teachers and students in class X-H. The data were collected through classroom observation and interview methods. From the data obtained, it is known that the utilization of YouTube and Wordwall in Arabic learning in class X-H MAN 2 Yogyakarta is carried out within the framework of introducing new mufradat starting from providing stimulants in the form of songs to vocabulary mastery exercises. In the series of using these two media, the advantages and disadvantages based on the perspectives of Arabic language teachers and students are also revealed. Some of the shortcomings have been realized from the beginning by Arabic teachers and strategic efforts have been made to overcome them.